Perangkat Penilaian Kinerja untuk Pembelajaran Teknik Pemeliharaan Ikan - Ardli, Imam; Abdullah, Ade G.; Mudalifah, Siti; Ana, Ana (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2012)
This paper shows the study result of performance assessment instrument development for the learning of fish-rearing technique. The study was intended to develop the new performance assessment instrument and to determine teachers’ and students’ responses toward its using. The study adapted development research procedures by selecting 27 students as the sample. Before the instrument was applied, it was tested by some experts. The result of feasibility test showed that the performance assessment instrument was categorized very good, thus revision was not required. After that, the instrument was experimented to several students. The findings showed that according to the teachers, the media attainment level was classified very good; however, the students argued that the instrument was good. Therefore, it was concluded that the performance assessment instrument was able to improve students’ interest toward practical work, to motivate students in learning, and to help them in scoring. The researchers hope that the study can contribute to the quality improvement of performance assessment instrument in the learning process at vocational secondary school.